Mathematical Critical Thinking Ability of Grade IX Students in Solving Ill-Structured Problems - Umbara, Hanifa Dina Aulia Dewi; Jupri, Al; Dahlan, Jarnawi Afgani (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
Students' mathematical critical thinking ability (MCTA) in Indonesia is still low, and one contributing factor is that students are not accustomed to solving non-routine problems, including ill-structured problems. This research aimed to explore the mathematical critical thinking ability (MTCA) in solving ill-structured using a qualitative approach with a case study method. This research involved 24 grade IX students from a junior high school in Bandung City, Jawa Barat Province, who had learned quadratic equations. Data were collected through a written test on MCTA and follow-up interviews. The results reveal that students fail to meet the MCTA indicators due to their lack of practice in solving contextual problems on quadratic equations and ill-structured problems. In addition, to gain a deeper understanding of mathematical critical thinking ability and the ability to solve ill-structured problems, future researchers could use two separate instruments, as these abilities involve distinct cognitive processes: convergent thinking and divergent thinking.